The University and its libraries: reactions and resistance to scientific publishers - Bastos, Flavia [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio; Oddone, Nanci (Ios Press, 2012)
This paper addresses the relationship of copyright and the right of universities on scientific production. Information and Communication Technologies (ICTs) are causing many changes in the system of scientific communication, such as the creation of Institutional Repositories that aim to gather scientific production in digital format. The University needs quicker ways of spreading academic production and many questions are emerging due to contexts such as the Open Access movement. Thus, this paper questions the positioning of Universities, especially Public Universities, which despite having policies related to intellectual property to protect the transferring forms of research results to society; many times do not have a positioning or a mechanism that regulates the self-deposit of scientific production in these Institutional Repositories. In order to develop this paper, the following issues are addressed: lack of interest of the University in storing scientific production; reports on the relationship of the library with scientific publishing houses; the participation of faculty members and students in supporting the Free Access movement; and initiatives aimed at greater flexibility of copyright to the context of scientific production. In order to follow the development of these issues at international level, it was opted for qualitative research with non-participating direct observation to carry out the identification and description of copyright policy of important publishers from the ROMEO SHERPA site; therefore, it can be observed that there are changes regarding the publishers' flexibility before self-archiving of authors in open access institutional repositories in their universities. Given this scenario, we presente reflections and considerations that involve the progress and mainly the integration of the University and its faculty members; the institution should recommend and guide its faculty members not to transfer their copyrights, but to defend their right of copy to Institutional Repositories along with Publishing Houses.
Keywords: Institutional Repositories; Copyright; Electronic Scientific Communication; Public University; Open Access Movement